Exploring Colonial mimicry in Affifudin Omar’s Paradoks - Nurhanis Sahiddan,; Hashim Ismail,; Tengku Intan Marlina Tengku Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper utilises the conceptual framework of Homi K. Bhabha’s mimicry to explain the elements of mimicry from the portrayal of the Muslim Malay characters in Affifudin Omar’s novel, Paradoks (2011) and to determine their resistance to colonial discourse. The conceptual framework is explicated into three major elements for the analysis of the novel in terms of: a) contesting colonisation, b) metonymy of presence, and c) splitting of colonialist discourse. A textual analysis of the novels has been conducted to examine whether the Muslim Malay characters possess elements of mimicry as colonial discourse and resist them with their Islamic beliefs. The results show that the Muslim Malay characters are mimic characters, but their Islamic beliefs lead to their spiritual successes. Their Islamic beliefs function as a tool for resisting colonial discourse and emancipation from colonial power. This paper is an expansion of research in colonial mimicry and Malay literature to resist colonial discourse.